Bilateral Ulnar-Sided Wrist Pain due to Pisiform-Hamate Coalition. (27th November 2019) - Nolte, Ingo; Mauler, Flavien; Sánchez, Tomás
Abstract : Coalition between the pisiform and the hamate is a rare congenital anomaly, often presenting as an asymptomatic incidental finding on radiographs. In some cases, it may become symptomatic, typically after trauma. We present a 13-year-old patient, with no history of trauma, presenting a bilateral painful coalition of the pisiform and hamate. Both of which were treated with excision of the pisiform resulting in complete pain relief. Pisiform-hamate coalition is a rare condition, which can become symptomatic even without any trauma or overuse activity, and is an important differential diagnosis in ulnar-sided wrist pain.